Protective effects of L-glutamine against toxicity of deltamethrin in the cerebral tissue - Varol S (Dove Medical Press, 2016)
Sefer Varol, Hasan Hüseyin Özdemir, Mehmet Uğur Çevik, Yaşar Altun, Ibrahim Ibiloğlu, Aysun Ekinci, Aslıhan Okan Ibiloğlu, Metin Balduz, Demet Arslan, Recep Tekin, Fesih Aktar, Mehmet Ufuk Aluçlu Department of Neurology, Faculty of Medicine, Dicle University, Diyarbakir, Turkey Background: Deltamethrin (DLM) is a broad-spectrum synthetic dibromo-pyrethroid pesticide that is widely used for agricultural and veterinary purposes. However, human exposure to the pesticide leads to neurotoxicity. Glutamine is one of the principal, free intracellular amino acids and may also be an antioxidant. This study was undertaken in order to examine the neuroprotective and antioxidant potential of L-glutamine against DLM toxicity in female Wistar albino rats. Materials and methods: The rats were divided into the following groups (n=10): Group I: control (distilled water; 10 mL/kg, po one dose), Group II: L-glutamine (1.5 g/kg, po one dose), Group III: DLM (35 mg/kg, po one dose), and Group IV: DLM (35 mg/kg, po one dose) and L-glutamine (1.5 g/kg, po one dose after 4 hours). Total oxidant status (TOS), total antioxidant status (TAS), tumor necrosis factor-α, interleukin (IL)-1β, and IL-6 levels and apoptosis were evaluated in brain tissue. Results: DLM-treated animals had a significant increase in brain biochemical parameters, as well as TOS and TAS. Furthermore, the histopathological examination showed neuronal cell degeneration in the cerebral tissue. L-Glutamine treatment decreased the elevated brain levels of TOS and neuronal cell degeneration. There was no difference in tumor necrosis factor-α, IL-1β, and IL-6 levels between the groups. Conclusion: L-Glutamine may reduce the toxic effects of DLM in the cerebral tissue through antioxidant properties. Keywords: deltamethrin, L-glutamine, rat